Pengaruh Leverage, Ukuran Perusahaan, dan Financial Distress terhadap Konservatisme Akuntansi Sektor Pertambangan - Utami, Nurul Aulya Laily; Isnawati (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the effect of Leverage, company size, and Financial Distress on accounting conservatism in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This research employs a quantitative method using secondary data from the annual financial statements of 81 companies, representing the population, and 31 companies as the sample, selected through purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of STATA 17 software. The results show that Leverage has a significant negative effect on accounting conservatism, meaning that an increase in Leverage tends to decrease the application of accounting conservatism. Company size has no significant effect on accounting conservatism, although larger companies tend to apply higher conservatism, but this influence is not statistically significant. Financial Distress has a significant negative effect on accounting conservatism, indicating that companies experiencing financial difficulties tend to be less conservative in their financial reporting. The impact of this research contributes to a deeper understanding of the factors influencing accounting conservatism in the mining industry, and assists managers, investors, and creditors in making more informed decisions regarding financial reporting practices in the mining sector.